Factor the following: 1) xReturn to the tutorial^{2}+ 7x + 6 Following the explicit rules, a = 1, b = 7, c = 6 in this case. ac = (1)(6) = 6. So we need to find the two factors of 6 that add up to 7. Factors of 6 are: 1 and 6, -1 and -6, 2 and 3, -2 and -3 Factors of 6 that add up to 7 are +1 and +6. Thus, split 7x into x + 6x. x^{2}+ 7x + 6 = x^{2}+ x + 6x + 6 = x(x + 1) + 6(x + 1) = (x + 1)(x + 6) 2) 4x^{2}+ 5x - 6 a = 4, b = 5, c = -6 ac = (4)(-6) = -24 Factors of -24 that add up to 5 are +8 and -3 Thus, 5x = 8x - 3x 4x^{2}+ 5x - 6 = 4x^{2}+ 8x - 3x - 6 = 4x(x + 2) - 3(x + 2) = (x + 2)(4x - 3)